Venture Capitalists, Asymmetric Information, and Ownership in the Innovation Process - Simona Fabrizi; Steffen Lippert; Peh Norbäck; Lars Persson (Research Institute of Industrial Economics (IFN), 2008)
In this paper we construct a model in which entrepreneurial innovations are sold into oligopolistic industries and where adverse selection problems between entrepreneurs, venture capitalists and incumbents are present. We show that as exacerbated development by better-informed venture-backed rms is used as a signal to enhance the sale price of developed innovations, venture capitalists must be sufciently more efficient in selecting innovative projects than incumbents in order to exist in equilibrium. Otherwise, incumbents undertake early preemptive, acquisitions to prevent the venture-backed rms' signaling-driven investment, despite the risk of buying a bad innovation. We nally show at what point the presence of active venture capitalists increases the incentives for entrepreneurial innovations.
Keywords: C70; D21; D82; G24; L20; M13; O30; 330; Venture Capitalists; Innovation; Entrepreneurs; Signaling; Development; Risikokapital; Innovation; Eigentümerstruktur; Signalling; Übernahme; Theorie